LITHOLOGICAL FEATURES OF DEVONIAN DEPOSITS OF THE DOBROGEAN FOREDEEP AND ASSESSMENT OF POTENTIAL OIL AND GAS RESERVOIR ROCKS’ OCCURRENCE - Radkovets, N.; Koshil, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Petrographic investigations of Devonian strata of the Dobrogean Foredeep were performed. It was established that the Lower Devonian deposits of the Lochkovian are represented by clay-carbonate lithofacies, which by its petrographic characteristics are a continuation of the Upper Silurian strata. Lithofacies, which belong to Pragian-Emsian age, are made up of terrigenous reddish-brown sandstones, siltstones and argillites, which are the age equivalent of the continental Devonian deposits, the so-called "Old Red Sandstones". Deposits of the Middle Devonian (Eifelian, Givetian stages) as well as Upper Devonian (Frasnian, Famennian stages) represent typical carbonate platform sediments and are mainly made up of organogenic-detritic limestones, which underwent the partial or complete dolomitization and sulphatization. Devonian deposits are spread in the Dobrogean Foredeep and partly outside it. Generally they show monoclinal folding and their thickness increases towards the dipping of the Foredeep. Carbonate rocks of Middle and Upper Devonian are cavernous, fractured, porous, which allows considering them as potential oil reservoir rocks, whose oil-bearing is confirmed by the existence of two fields – Zhovtoyarske and Skhidno-Saratske. Apart from the Middle and Upper Devonian the favorable reservoir properties and hence the gas prospects have the terrigenous rocks of the Lower Devonian.